Effects of different interventions on smoking cessation in chronic obstructive pulmonary disease patients: A systematic review and network meta-analysis. (December 2022) - Wei, Xuefeng; Guo, Kangle; Shang, Xue; Wang, Shizhong; Yang, Chaoqun; Li, Jieyun; Li, Yanfei; Yang, Kehu; Li, Xiuxia; Zhang, Xiaohui
Abstract: Background and objectives: Smoking is responsible for 9 out of 10 deaths related to chronic obstructive pulmonary disease, and this number can be reduced by quitting smoking. In this study, the effect of different interventions on smoking cessation of patients with chronic obstructive pulmonary disease was assessed through a network meta-analysis. Methods: Eight databases were searched to obtain randomized controlled trials involving different interventions for smoking cessation in chronic obstructive pulmonary disease patients. The Cochrane Handbook tool was employed to assess the risk bias of included studies. Network meta-analysis was performed using STATA software. Results: A total of 23 studies involving 13, 480 patients were included. Eight studies were rated as having a high risk of bias, seven studies had a low risk, and in eight studies, the risk was unclear. All studies employed 13 different interventions, including eight monotherapies and five combination therapies. Network meta-analysis showed that a combination of behavioral therapy and pharmacotherapy was superior in achieving patients' smoking cessation compared to monotherapy. Moreover, varenicline was more helpful for smoking cessation than other single interventions. The final surface under the cumulative ranking curve value indicated that cognitive behavior therapy combined with bupropion achieved the best smoking cessation effect. Conclusions: The obtained results indicate that a combination of behavioral therapy and pharmacotherapy is most powerful in helping chronic obstructive pulmonary disease patients to quit smoking. Researchers should focus more on the safety of pharmacotherapeutic interventions. Moreover, more high-quality trials investigating the stability of evidence levels of different interventions on abstinence must be conducted.